The Impact Of Human Resource Information System (HRIS) On Human Resource (HR) Performance - Aini Akma Rasyidah, Mohd Sufi (Universiti Malaysia Sarawak (UNIMAS), 2020)
Human resource information system application is important for human resource performance to function effectively. This research investigated the impact of the three most current searched human resource information modules such as recruitment and selection, performance appraisal, compensation benefit the effectiveness towards human resource performance. The research has been conducted among 95 employees at Sarawak State Library, The Sarawak Foundation and Jabatan Agama Islam Sarawak. A pilot test was conducted among 35 respondents of employers and employees from the first two organization selected shows all the listed questionnaire is reliable and accepted for the research. For actual study, different data on managers, executives, HR professionals, IT developer and employees with HRIS usage knowledge (N=70) were analysed using different SPSS analysis. The research also focused on which HRIS modules have the most dominant impact among the technology functions. The results that are determined, there is significant impact of HRIS on HR Performance and there is significant dominant factor related to the research. In this research, HRIS compensation and benefits. This results highlight the significant of HRIS modules in direct description of the particular HR functions to add more source and further understanding to academician, HR professional, employers and whole organizations about the changing technology application especially in changing HRIS application functions and needs in the organization. Most importantly HRIS management team that contributes largely in optimizing the HRIS.